(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In view of the necessity of the time, “Make in India” was launched by the Hon’ble Prime Minister India’s on Aug fifteen, 2014. The Prime Minister invited to both international and domestic industrialists, “Make in India” campaign is actually aimed to create the nation a manufacturing hub which will help increase development and work. The current analysis is based on secondary details. The information has been extracted from the different energy sources as research articles, publications from the Ministry of Commerce, Government of India, different bulletins of RBI and authenticated sites. The study discovered that Make in India is going to bring a radical change in different areas. As a result, we are able to conclude that, despite the reality that Makes in India however arrived at a proper time, the execution of its remains a huge challenge.